49 Rapid Access AF Clinic – A New Service Towards Better Outcome. (3rd June 2016) - Sekar, Baskar; Whyler, Jonathon; Williams, Emma; Azzu, Abdul; Payne, Mark; Hanna, Azad
Abstract : Introduction: Atrial fibrillation (AF) is one of the top ten reasons for hospital admissions. Failure to recognise this arrhythmia and risk stratify patients early on diagnosis can have detrimental consequences including high risk of thromboembolic events, stroke, heart failure and death. An audit conducted in our hospital (2011–2012) revealed that patients with AF stay an average 5.6 days in hospital. It has been estimated that billions of pounds are spent each year from health and social care budgets due to AF and AF related strokes. 1 To address this, a new service "Rapid access AF clinic (RAAFC)" was developed in our hospital in June 2012. This retrospective study explores the role of RAAFC on clinical outcomes since its introduction. Methods: 210 patients were seen in our clinic between 01/06/2012 and 30/10/2015. 56 patients were excluded from the analysis - – 41 due to lack of access to records, 1 found to be in CHB and 14 in sinus rhythm. 154 patients were included in the final analysis. Patients were divided in to 2 groups depending on the duration of their symptoms. Group A (symptoms <48 h, n = 49) were seen in clinic on the same day. After clinical assessment, patients were cardioverted with flecanide and if failed underwent electrical cardioversion. Group B (symptoms >48 h, n = 105) were advised rate control medications, anticoagulants and arranged for cardioversion after 6 weeks when maintained in therapeutic INR. Those with poor rate control or early signs of instability, underwent TOE guided cardioversion. Follow-up ranged from 3 months to a year. Results: The mean age of the patients was 63.8 ± 13.8 years and 67.5% were male. Patients characteristics at baseline are shown in Table 1 and final outcomes in Table 2 . Worryingly 57.1% of the patients scored 2 or above on CHADS2Vasc risk assessment of which 61.4% were not on anticoagulants. During follow-up, a high proportion of patients (63.9%) were asymptomatic and 66.7% maintained in sinus rhythm. The average length of stay was 2.72 ± 8.44 h. Only 4 patients (0.04%) were readmitted prior to their initial follow-up due to recurrence of AF. Two patients in group B developed complications related to thromboembolism. One had left femoral artery embolism requiring embolectomy and the other had TIA 2 days following TOE guided cardioversion. The patient who had embolic event had CHADS2Vasc score of 2 and developed symptoms 3 days after commencing warfarin when INR was subtherapeutic. Conclusions: RAAFC appear very effective in preventing hospital admissions, reduce length of stay and also helpful in identifying high risk patients who benefit from anticoagulation. We recommend RAAFC initiated in each trust to lower morbidity, mortality and also costs to NHS. Reference: Camm AJ, Kirchhof P, Lip GY, et al. Guidelines for the management of atrial fibrillation. The task force for the management of atrial fibrillation of the European Society of Cardiology. Eur Heart J . 2010;31(19):2369-–429